1995
DOI: 10.1111/j.1532-5415.1995.tb07325.x
|View full text |Cite
|
Sign up to set email alerts
|

Older Age and the Underreporting of Depressive Symptoms

Abstract: Some older patients with clinically significant depression underreport their symptoms. When asking older patients about depressive symptoms, clinicians should view negative responses only within larger clinical contexts and should obtain information from other sources as needed. Similar concerns must temper interpretation of research that relies on subject self-report to study depression in late life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
116
3
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(122 citation statements)
references
References 32 publications
2
116
3
1
Order By: Relevance
“…(21) is a reliable and validated intervieweradministered measure of depressive symptom severity within the previous week that has been used with older adults in primary care (34). Because the HDRS is not based solely on patient self-report, it reduces measurement problems associated with the underreporting of some depressive symptoms on self-report inventories (36). However, many HDRS items assess somatic symptoms and are likely to be endorsed as a reflection of physical disease, not depression, which could spuriously increase the correlations between the HDRS and the cumulative illness burden.…”
Section: Samplementioning
confidence: 99%
“…(21) is a reliable and validated intervieweradministered measure of depressive symptom severity within the previous week that has been used with older adults in primary care (34). Because the HDRS is not based solely on patient self-report, it reduces measurement problems associated with the underreporting of some depressive symptoms on self-report inventories (36). However, many HDRS items assess somatic symptoms and are likely to be endorsed as a reflection of physical disease, not depression, which could spuriously increase the correlations between the HDRS and the cumulative illness burden.…”
Section: Samplementioning
confidence: 99%
“…In addition, patients with multiple conditions may be overlooked due to the focus on physical rather than mental symptoms [12]. However, this 'crowding out' hypo thesis has been refuted [9]. A common factor may be inadequate time as those with comorbidities often require more time than physicians feel is available.…”
Section: Why Do Physicians Have Difficulty Diagnosing Depression In Tmentioning
confidence: 99%
“…For example, some studies report that older patients may be more likely to believe that depressive symptoms are a normal part of life and may be more reluctant to volunteer psychological or emotional symptoms [9]. It has been stated that late-life depression tends to present with vague symptoms or masked depression (i.e., depression without overt low mood) and it is also widely taught that in older people somatic symptoms may account for higher scores on depression severity measures [10].…”
mentioning
confidence: 99%
“…Physicians may believe that older adults suffering from suicidality are noncompliant with treatment (130) and may tend to be reluctant to refer older patients with depression for mental health care (131). The tendency of older adults to minimize or underreport depressive and suicidal symptoms may further impede risk detection (132)(133)(134)(135). Isometsä and others found that only 11% of those seen in primary care in the month prior to suicide communicated suicidal intent, although this was not exclusive to older adults (136).…”
Section: Randomized Treatment Trials With At-risk Older Adultsmentioning
confidence: 99%